CHARACTERIZATION OF THE ARCHITECTURE OF RED BRICKS FROM THE END OF 19TH CENTURY UNTIL THE BEGINNING OF THE 20TH CENTURY ON THE TERRITORY OF LATGALE REGION - Keivisa, Julija; Strode, Aina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The term “style of bricks” often is used to name one of the formal stylistic trends of 19th century or the beginning of 20th century which on the whole construction's background differs with its wall facades made only from bricks. The aim of the paper is to investigate and analyze the most remarkable examples of red bricks architecture of the end 19th century and the beginning of 20th century in Latgale region. The methods used in the research are based on the study of scientific and publicistic sources which discover evidences in architecture of the epoch.